Mechatronics - Davim, J. Paulo (ISTE., 2011)
The term Mechatronics is a combination of the words mechanics and electronics . It is the blending of mechanical, electronic, and computer engineering into an integrated design and implementation. Mechatronics systems employ microprocessors and software as well as special-purpose electronics.